Experiment of Magic Fish Set in Motion by Electricity - Ward, Lock (Wonders of electricity and the elements, being a popular account of modern electrical and magnetic discoveries, magnetism and electric machines, the electric telegraph and the electric light, and the metal bases, salt, and acids, 1870)
Illustration depicting an apparatus used to animate tin fish through the use of an electro-magnet.
Keywords: Electricity; Magnetism; Scientific illustration; Science--Study and teaching; Science--Experiments; Electric toys